Slovenski podjetniški observatorij 2005 - Rebernik, Miroslav; Tominc, Polona; Duh, Mojca; Rus, Matej; Krošlin, Tadej; Pušnik, Ksenja; Bradač Hojnik, Barbara; Močnik, Dijana (University of Maribor Press, 2006)
Slovenian Entrepreneurship Observatory 2005. Slovenian Entrepreneurship Observatory 2005 shows some aspects of Slovenian entrepreneurship in the previous year. We provide the basic features of Slovenian companies, as can be seen from the economic and statistical data. The analysis included all those companies, which in 2004 submitted the annual reports at AJPES. We have analysed four topics: 1) evaluated the ambitions of established entrepreneurs in Slovenia with regard to their future growth in comparison with the growth ambitions of emerging and new entrepreneurs; 2) analysed the cooperation and partnerships between enterprises, reasons, forms and areas of cooperation and impacts of the effectiveness of cooperation on the competitiveness of small and medium-sized businesses compared with large enterprises in Slovenia; 3) analysed the differences in age, size, export orientation, performance and aspirations for growth between family and non-family small and medium-sized enterprises in Slovenia; 4) studied the internationalization of small and medium-sized enterprises, and added a survey of major works by Slovenian authors who have written about entrepreneurship in 2005.